A projection strategy for improving the preconditioner in the LOBPCG - Ma, Tailai; Sun, Shuli; Zheng, Fangyi; Chen, Pu (Zielona Góra: Uniwersytet Zielonogórski)
The computational methods for solving the generalized eigenvalue problems of real symmetric matrices are crucial in fields such as structural dynamics analysis. As the scale of the problems to be solved increases, higher efficiency in solving eigenvalue problems is demanded. The LOBPCG (locally optimal block preconditioned conjugate gradient) method is a promising iterative algorithm suitable for solving large-scale eigenvalue problems, capable of quickly solving multiple extreme eigenpairs.
Keywords: LOBPCG; preconditioner; preconditioned conjugate gradient (PCG); projection method